Development Of Personalized Learning Environment (PLE) For Malaysian School Environment Based On ADDIE Model - Che Ku Mohd, Che Ku Nuraini; Shahbodin, Faaizah (Council for Innovative Research, 2014)
Personalized Learning Environment (PLE) is a new concept in designing and developing an online learning. PLE is more focused on individual learning rather than the instructor, facilities, resources and tools. PLE has also played an active role in improving the effectiveness of learning. This paper aims to share the development and preliminary findings on PLE in teaching Form 2 Science. The samples involved are Form 2 students at secondary schools. The study group was composed of 90 students. The topic chosen is Nutrition. In this study, the development process of the environment was examined according to the Analyze, Design, Develop, Implement, Evaluate, Instructional Design Model (ADDIE). There are divided into three phases. Phase one is Analysis which includes literature survey and collection of preliminary analysis data. Second phase is Designing and Development which adopt ADDIE model as a basis for multimedia development. The last phase is Testing and Evaluation.